A morphometric analysis of the forelimb in the genus Tapirus (Perissodactyla: Tapiridae) reveals influences of habitat, phylogeny and size through time and across geographical space. Issue 2 (10th May 2018) - Maclaren, Jamie A; Hulbert, Richard C; Wallace, Steven C; Nauwelaerts, Sandra
Abstract: The limb skeleton of tapirs (Perissodactyla: Tapirus spp.) was traditionally thought to exhibit morphological variation only as a result of changes in body size. Here, we test whether forelimb variation exhibited by Tapirus is solely an artefact of size fluctuations through the tapir fossil record or whether it is influenced by habitat differences. We investigated the forelimb osteology of 12 species of Tapirus using three-dimensional geometric morphometrics on laser surface scans. Aligned shape coordinates were regressed against intrinsic bone size to account for allometry. Taxa of equivalent body mass exhibited significant differences in size-corrected bone shape. Stable carbon isotope values were averaged per species as a proxy for habitat density. Multivariate regressions of the humerus, pisiform, cuneiform, unciform, third and fourth metacarpals revealed no significant influence of size on shape. The lateral carpals (pisiform, cuneiform, unciform) demonstrated variation across the habitat density gradient. Observed variation is likely driven by species in the extinct subgenus Helicotapirus tapirs, which inhabited drier, more open woodland than modern taxa. We conclude that tapir forelimb variation is not exclusively an artefact of body size, with lateral wrist bones displaying notable differences across a habitat density gradient, beyond that resulting from size and phylogenetic effects.